2013
DOI: 10.1055/s-0033-1351668
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Magnetic Resonance Angiography in Vascularized Groin Lymph Node Transfer: An Anatomic Study

Abstract: Vascularized groin lymph node transfer (VGLNT) has been successfully used to treat lymphedema. However, lack of familiarity with the inguinal node anatomy and concerns regarding donor site morbidity have limited its widespread use. The purpose of this study was to use magnetic resonance angiography (MRA) to clarify the inguinal anatomy and provide a reliable method for identifying the location of the superficial transverse inguinal lymph nodes. In this study MRA was used to evaluate the superficial inguinal ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 22 publications
(31 reference statements)
1
61
0
2
Order By: Relevance
“…Caplan studied the lymphatic drainage of the great toe in 50 human fetuses and found drainage to these nodes in nine cases. 60 In another study in patents with malignant melanoma of the lower limb, the sentinel node was located in the superolateral zone in 5 percent of the cases. 58 Direct injection studies in adult human cadavers by the current authors revealed that the superolateral nodes were the primary nodes draining the local collectors of the thigh; the latter originate from the watershed area of the posterior thigh.…”
Section: Risk Of Iatrogenic Lymphedemamentioning
confidence: 96%
“…Caplan studied the lymphatic drainage of the great toe in 50 human fetuses and found drainage to these nodes in nine cases. 60 In another study in patents with malignant melanoma of the lower limb, the sentinel node was located in the superolateral zone in 5 percent of the cases. 58 Direct injection studies in adult human cadavers by the current authors revealed that the superolateral nodes were the primary nodes draining the local collectors of the thigh; the latter originate from the watershed area of the posterior thigh.…”
Section: Risk Of Iatrogenic Lymphedemamentioning
confidence: 96%
“…19 Recently, magnetic resonance angiogram imaging has been used to evaluate the location of the transverse superficial inguinal lymph nodes. 22 All nodes were located deep to Scarpa's fascia and the mean distance of the nodes from the anterior superior iliac spine (ASIS) toward the pubic tubercle (PT) was 9.1 cm, and 3.1 cm in a perpendicular axis below that line. About 68% of the superficial inguinal nodes were located within a 3-cm radius of that epicenter, with clustering at the junction of the superficial inferior epigastric and superior circumflex iliac veins (67% within the venous bifurcation).…”
Section: Donor Site Groinmentioning
confidence: 98%
“…This technique, combined with further Doppler confirmation of superficial circumflex vessels and reverse lymphatic mapping using Technetium and indocyanine green, has allowed for 35 successful lymph node transfers without donor site lymphedema. 22 Vessel anastomosis differs in terms of flap choice. In cases where VLNT alone is performed, the superficial circumflex iliac vessels are anastomosed to recipient vessels.…”
Section: Donor Site Groinmentioning
confidence: 99%
“…Because these procedures are routinely performed on young, often female patients with an increased body mass index, the avoidance of unnecessary radiation exposure is of high importance, especially in those who already have been diagnosed with cancer. Second, high-resolution MR imaging (with similar spatial resolution to that of CT) can be achieved by using contrast agents with longer intravascular retention times, such as gadofosveset trisodium (Ablavar; Lantheus Medical Imaging, North Billerica, Mass) (15). Third, dynamic vascular information can be obtained, if needed, by using time-resolved angiography or other techniques for the assessment of inflow and outflow patterns.…”
Section: Mr Angiographymentioning
confidence: 99%